Bergenin Monohydrate Attenuates Inflammatory Response via MAPK and NF-κB Pathways Against Klebsiella pneumonia Infection - Tang, Qihe; Wang, Qingyu; Sun, Zhuojian; Kang, Songyao; Fan, Yimeng; Hao, Zhihui (Frontiers in Pharmacology, 2021)
Background: Klebsiella pneumonia (Kp) has emerged as a critical pathogen causing severe clinical problems, such as pneumonia and sepsis. Meanwhile, intensified drug resistance induced by antibiotic therapy necessitates discovering novel and active molecules from Traditional Chinese Medicine (TCM) for treatment. Methods and results: In this study, the isolated Bergenin monohydrate (Bm) showed an anti-inflammatory effect in Klebsiella-infected mice. We initially investigated the anti-inflammatory effects and cytoprotection against oxidative stress in vitro and in vivo. Interestingly, a specific dose of Bm can effectively ameliorate lung injury and suppress the expression of inflammatory cytokines such as TNF-α, IL-6, IL-1β and PEG2. Moreover, Bm was also shown to reduce the levels of MPO, MDA and increased SOD and GSH activities. Moreover, we assessed the intracellular signaling molecules including p38, ERK, JNK, IκB, NF-κB-p65 by western blotting and verified through MAPK and NF-κB pathways inhibition experiments. These results reveal that Bm executed its effects via the classical MAPK signaling pathway and NF-κB pathway. Conclusions: Given its underlying anti-inflammatory effect, Bm may be used as a promising therapeutic against Klebsiella-induced infection, thus providing a benefit for the future clinical therapy of pneumonia and medicine design.